2002
DOI: 10.1002/art.10426
|View full text |Cite
|
Sign up to set email alerts
|

The safety of celecoxib in patients with aspirin‐sensitive asthma

Abstract: Objective. To determine whether celecoxib, a selective cyclooxygenase 2 (COX-2) inhibitor, cross-reacts in patients with aspirin-exacerbated respiratory disease (AERD) with asthma.Methods. Sixty patients with asthma underwent double-blinded, placebo-controlled oral challenges with celecoxib (100 mg, 200 mg, and 2 placebos) over 48 hours in our General Clinical Research Center. The next day, sensitivity to acetylsalicylic acid (ASA) was proven in all patients with the use of single-blinded ASA challenges.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(52 citation statements)
references
References 30 publications
(35 reference statements)
3
48
0
1
Order By: Relevance
“…Reactions to acetaminophen are unusual but can occur. [28][29][30][31][32] The dogma indicates that reactions in patients with AERD are triggered by the inhibition of COX-1, which is not a biologic activity of nonaspirin salicylates and, as such, dietary salicylates are generally not thought to trigger reactions. However, results of recent research showed that a low-salicylate diet perhaps leads to a reduction in symptoms in some patients with AERD.…”
Section: Chronic Sinusitis With Npsmentioning
confidence: 99%
“…Reactions to acetaminophen are unusual but can occur. [28][29][30][31][32] The dogma indicates that reactions in patients with AERD are triggered by the inhibition of COX-1, which is not a biologic activity of nonaspirin salicylates and, as such, dietary salicylates are generally not thought to trigger reactions. However, results of recent research showed that a low-salicylate diet perhaps leads to a reduction in symptoms in some patients with AERD.…”
Section: Chronic Sinusitis With Npsmentioning
confidence: 99%
“…Impaired EP receptor input compromises control of TP receptor signaling by PKA (28), increasing the adherence of platelets to granulocytes, inducing endothelial ICAM-1 (28), activating 5-LO, and enabling platelet-adherent leukocytes to mediate LT generation (9). The residual local PGE 2 derives principally from COX-1, which may explain why only COX-1 active drugs provoke clinical reactions (6) and why COX-2-selective drugs are well tolerated by these patients (20). The MC activation typical of clinical reactions (50,63,64) may be due to the agonistic effects of cysLTs derived from intrapulmonary platelet-granulocyte complexes when residual PGE 2 is depleted.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
“…The dependency on COX products to maintain homeostasis over 5-LO activity is a unique feature of AERD. Remarkably, subjects with AERD can tolerate selective antagonists of COX-2 (20), suggesting that the homeostatic prostaglandins derive principally from COX-1.…”
mentioning
confidence: 99%
“…Reports suggest that COX-2 selective NSAIDs may be safer than nonselective NSAIDs in aspirin-sensitive asthmatics. 72 NSAIDs, including COX-2 selective drugs, may also exacerbate inflammatory bowel diseases.…”
Section: Pfizer Suspended the Sale Of Valdecoxib In 2005 Following Fomentioning
confidence: 99%